Pengaruh Interaksi Parasosial Terhadap Hubungan Parasosial, Kredibilitas Endorser Dan Niat Beli Penggemar Syahrini Terhadap Produk Kosmetik Di Media Instagram - Anindyasari, Yurike; Kusumasondjaya, Sony (Arthavidya Jurnal Ilmiah Ekonomi, 2019)
The number of Instagram users continue to grow from year to year and so parasocial concept does. Parasocial concept itself is getting popular to those who study media. Nowdays, parasocial concept is used a lot more in daily lives by marketeers. Marketeers compete to pick the most influencial person who has the ability to attract others in order to promote special products/brands. This study was aimed at examining the influences of parasocial interaction, parasocial relationship, endorser credibility, and purchase intention of Syahrini’s fans on a make-up product. This research was a quantitative research using online questionnaire. Data were collected through online questionnaire and filled by Syahrini’s fan base on Instagram. The sample of this study used Syahrini’s women fans who never have bought a typical of make-up product (Lakme make-up) before. Later on, respondents were required to watch a short video about Syahrini before they finally filled the online questionnaire. A significant influence between parasocial interaction and parasocial relationship; a significant influence between parasocial relationship and endorser credibility; a significant influence between parasocial relationship and purchase intention; and a non significant influence between endorser credibility and purchase intention. The implication practice of this study is marketeers should choose the most ideal public figure, especially the one who could build such a strong relationship with fans. Also marketeers should be more innovative in creating new ways of communicating between fans and their idols.